Frontispiece: Functional Liquid Crystal Elastomers Based on Dynamic Covalent Chemistry. Issue 70 (16th December 2022) - Valenzuela, Cristian; Chen, Yuanhao; Wang, Ling; Feng, Wei
Abstract : Liquid crystal elastomers (LCEs) have been known as compelling functional polymers due to their unprecedented properties such as molecular anisotropy, superior responsive characteristics and reversible shape memory actuation. However, these outstanding properties have to do with permanent crosslinking networks that strongly restrict the scope of their applicability. In this Review article 10.1002/chem.202201957, Prof. L. Wang and Prof. W. Feng et al. address this issue by discussing the marriage of LCEs with dynamic covalent chemistry as a new paradigm for the development of advanced functional polymers with fascinating adaptive and dynamic features, which are of paramount significance for many emerging smart applications such as adaptive optics, soft robotics, bioinspired camouflage, 3D/4D printing technology, and beyond.